Contribuições ao projeto arquitetônico de edifícios em alvenaria estrutural - Rauber, Felipe Claus (2005)
The project, constituting one of the initial stages of the construction process and defining the building s characteristics, influences decisively to the execution of the work and the performance of the built environment. The adoption of a rationalized constructive system provides quickness, facility and quality to the construction, and, consequently, a better building performance if compared with traditional ways of construction. Therefore, the structural masonry, system whose rationalization comes from modular coordination and integration from the projects, has been increasingly used in Civil Construction. In Brazil, although, the resistance for its adoption resides, most times, in the lack of knowledge about the structural masonry constructive techniques proper from the system, and the fear of abandoning the connected with reinforced concrete, already dominated and accepted. Allied to this fact, comes the necessity of specific literature directed to the architects, responsible for the project idealization. To search for quality of building, this work propose the application of the principles of building s constructability and performance for projects elaboration, and shows the main points about the practice of the structural masonry projects, addressing the explanation to the architects